Adjustment of intrastromal corneal ring segments after unsuccessful implantation in keratoconic eyes - Monteiro, Tiago (2018)
To evaluate visual, refractive, and corneal topography outcomes in eyes with keratoconus that have undergone exchange/adjustment surgery with a new intrastromal corneal ring segment (ICRS) combination after unsuccessful visual and/or refractive outcomes after primary ICRS surgery.